1993
DOI: 10.1242/jcs.106.4.1023
|View full text |Cite
|
Sign up to set email alerts
|

Gene deletion suggests a role for Trypanosoma Cruzi surface glycoprotein gp72 in the insect and mammalian stages of the life cycle

Abstract: We have explored the biological function of a surface glycoprotein (GP72) of Trypanosoma cruzi by studying a null mutant parasite, generated by targeted gene deletion. GP72 deletion affected parasite morphology in several stages of the life cycle. Insect midgut (epimastigote) forms had a detached flagellum (apomastigote) in the null mutant. The abnormal flagellar phenotype persisted during development of the infective (metacyclic) forms but there was no impairment in the acquisition of complement resistance, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Little is reported about proteins mediating the interaction between T. cruzi epimastigotes and the insect hosts, but it has been observed that, on the anterior midgut surface, parasites were bound through the cell body or flagellum and, on the posterior midgut, only flagellar attachment to perimicrovillar membranes occurred . This attachment is presumably due to the involvement of glycoinositol phospholipid molecules. When a gene encoding a surface glycoprotein was deleted in those epimastigotes, a significant decrease of the parasite population attached to the triatomine vector Rhodnius prolixus was observed. , This may suggest the involvement of glycoproteins that are concentrated in the flagellar attachment zone in the process. In our study we could identify several putative uncharacterized proteins that are annotated and described by Blast2GO software as flagellar associated proteins (SI Table 1), which leads us to believe that, by the cell surface trypsinization and biotinylation methodologies employed here to analyze the cell surface proteome, one can detect the proteins that are involved in the parasite–vector interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is reported about proteins mediating the interaction between T. cruzi epimastigotes and the insect hosts, but it has been observed that, on the anterior midgut surface, parasites were bound through the cell body or flagellum and, on the posterior midgut, only flagellar attachment to perimicrovillar membranes occurred . This attachment is presumably due to the involvement of glycoinositol phospholipid molecules. When a gene encoding a surface glycoprotein was deleted in those epimastigotes, a significant decrease of the parasite population attached to the triatomine vector Rhodnius prolixus was observed. , This may suggest the involvement of glycoproteins that are concentrated in the flagellar attachment zone in the process. In our study we could identify several putative uncharacterized proteins that are annotated and described by Blast2GO software as flagellar associated proteins (SI Table 1), which leads us to believe that, by the cell surface trypsinization and biotinylation methodologies employed here to analyze the cell surface proteome, one can detect the proteins that are involved in the parasite–vector interaction.…”
Section: Resultsmentioning
confidence: 99%
“…41−43 When a gene encoding a surface glycoprotein was deleted in those epimastigotes, a significant decrease of the parasite population attached to the triatomine vector Rhodnius prolixus was observed. 44,45 This may suggest the involvement of glycoproteins that are concentrated in the flagellar attachment zone in the process. In our study we could identify several putative uncharacterized proteins that are annotated and described by Blast2GO software as flagellar associated proteins (SI Table 1), which leads us to believe that, by the cell surface trypsinization and biotinylation methodologies employed here to analyze the cell surface proteome, one can detect the proteins that are involved in the parasite−vector interaction.…”
Section: Epimastigote Cell Surface Proteomementioning
confidence: 99%
“…cruzi have been obtained in previous studies after targeted deletion of apparently unrelated, single-copy genes (Caler et al, 1998;Manning-Cela et al, 2001;Ribeiro de Jesus et al, 1993;Basombrı ´o et al, 2002;Garzon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not motility is essential for T. cruzi cytokinesis might be further explored by deleting genes such as PF16 or another CMF with a severe motility defect (Baron et al, 2007). A previous work with gp72-KO is also informative (de Jesus et al, 1993). In this report, the authors show that gp72 (FLA-1 in T. brucei) mutants have detached flagella, and the epimastigote mutants are able to differentiate into infective metacyclic forms (reduced compared with WT).…”
Section: Discussionmentioning
confidence: 79%
“…The lack of gp72 caused detached flagella and reduced metacyclogenesis. Though they were able to infect host cells in culture, they were not able to generate bloodstream trypomastigotes; instead, only amastigote forms were released (de Jesus et al, 1993;Cooper et al, 1993). The multicopy genes PFR-1 and PFR-2 were edited using CRISPR/Cas9 technology, and the null mutant also showed a detached flagellum, and they were unable to build the paraflagellar rod structure as shown by transmission microscopy (Lander et al, 2015).…”
Section: Introductionmentioning
confidence: 99%